What Matters for Choosing your Neighbors: Evidence from Canadian Metropolitan Areas - Kristian Behrens; Oualid Moussouni (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2019)
A corollary of the First Law of Geography and the Principle of Homophily is that "near things are more similar than distant things." We test that proposition using spatially fine-grained data on thousands of colocation patterns of ethnic groups in the six largest Canadian metropolitan areas. The geographic patterns reveal that groups that are more similar along various non-spatial dimensions- language, culture, religion, genetics, and historico-political relationships-colocate more. These results are robust to numerous controls and provide a quantitative glimpse of the 'deep roots' of homophily.
Keywords: 330